Deferral pattern in voluntary blood donors on basis of low hemoglobin and effect of application of digital hemoglobinometer on this pattern - Mathur, Ankit (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: One of the responsibilities of blood center is to provide safety to blood donors. It is mandatory to screen a blood donor for hemoglobin (Hb) or hematocrit which should not be less than 12.5 g/dl or 38% Hct. Most commonly applied method for hemoglobin estimation is copper sulphate method, but this method has chances of false acceptance as well as false deferral. In order to avoid this chance of error, digital hemoglobinometer is used. This study was planned to analyze effect of application of digital hemoglobinometer for detection of Hb on donors, who are deferred by copper sulphate method. MATERIALS AND METHODS: Total 35,339 voluntary non renumareted altruistic donors were included in this study between the periods of September 2005 to July 2006. Total deferred donors were 8622 (24.39%) and donors deferred due to hemoglobin by copper sulphate method were 4391 (50.92%). Digital hemoglobinometer was applied on 3163 deferred donors (72.03%). Results of digital hemoglobinometer were validated by known controls. RESULT: Digital hemoglobinometer was applied on 3163 donors who were deferred by copper sulphate method. Out of this, donors accepted by digital hemoglobinometer were 1196 (37.01%). Total repeat donors were 629 (52.50%) and first time were 567 (47.40%). Male donors were 891 (74.44%) and females were 305 (25.50%). Donors deferred with digital hemoglobinometer were 2135, out of them 1097 (51.14%) were repeat, 1038 (48.38%) were first time, 1349 (60.79%) were male, 786 (34.47%) donors were female donors. Range of hemoglobin in deferred donors was 7.0 to 12.4 and in accepted donors 12.5 to 16.4. CONCLUSION: By the application of digital hemoglobinometer 37.81% donors were found hemoglobin >12.5 which were deferred with copper sulphate method and unnecessary deferral of donors can be reduced to a great extent. In country like India, where blood supply is always less than the requirement, this new technique may be helpful to increase donor population but cost benefit ratio should be analyzed.